Second Line Therapy for Advanced Pancreatic Adenocarcinoma: Where Are We and Where Are We Going? - Brus, Christina; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2010)
Most patients with adenocarcinoma of the pancreas present with locally advanced or metastatic disease. Although single agent gemcitabine is widely accepted as first-line therapy, there is no current standard of care for gemcitabine-refractory patients. Common second-line chemotherapy regimens included oxaliplatin and 5-FU/leucovorin (OFF), gemcitabine and oxaliplatin (GEMOX), oxaliplatin and capecitabine (XELOX), and irinotecan-oxaliplatin. At the 2010 American Society of Clinical Oncology (ASCO) Annual Meeting, several new second-line chemotherapy regimens were presented, including gemcitabine and oxaliplatin with imatinib, single agent nab-paclitaxel, and the combination of high-dose capecitabine with oxaliplatin and sorafenib. These abstracts provide exciting new directions for the treatment of gemcitabine-refractory advanced pancreatic cancer. Image: Yale Cancer Center, Yale University School of Medicine. New Haven, CT, USA